Dummy rotation rate to assess hip throw and back throw execution quality in wrestling - Laptev, A. I.; Shipilov, A. A. (Theory and Practice of Physical Culture, 2018)
The study analyzes benefits of the modern biomechanical test equipment to rate the throw quality in the modern competitive wrestling sport, and offers a set of elementary move scoring criteria for the sport. The study data and analyses made it possible to find the statistically significant correlations (p<0.05) of the mean angular rate with amplitude (r = 0.60); maximal dummy rotation rate (r = 0.79) with the execution time (r = - 0.64) for the back throw. The same correlations are true for the hip throw albeit to a lesser degree, with r = 0.55, r = 0.68 and r = - 0.33, respectively, whilst no meaningful correlation was found for the mean angular rate versus the hip throw execution time. On the whole, the study data and analyses showed benefits of the mean angular rate being applied to assess the execution quality of at least these two throws. The objectively measurable criteria make it possible to improve the accuracy of the technical and special physical fitness tests in the wrestlers` training process and, hence, step up the process controllability and efficiency.